(3MbGFb GdObGFb Ydi QbGFb GdMbGFbs - (3MSjf Hf EHQGgje Hf MSf GdLHQJis; (3eMeO eMeO Hf CMeO, SHW GdeGQOjfj,J (B912 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLI deG bQCJ QSGdI GdObGFb ai MSGH GdOQL hGdObGFb ddYdGeI SHW GdeGQOjfi s
(3BNQgG (B:s
(3Je JbSje GdMGUd Ydi aVd GdHjJjf jMUd GdeWdhH s
(3ajgG HYV GdLOGhds
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B359 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B31 s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdadcs